MULTIFACETED CLINICAL PRESENTATION OF CAUDAL REGRESSION SYNDROME: A CASE REPORT AND LITERATURE REVIEW - Protsailo, Mykhailo Dmytrovych; Mudryk, Uliana Mykhailivna; Bidzilya, Pavlo Vasylovych; Hudak, Petro Stepanovych; Khlibovska, Oksana Ivanivna; Nikitina, Irуna Mykolaivna; Dzhyvak, Volodymyr Heorgiyovych (Eastern Ukrainian Medical Journal, 2025)
The purpose of the study is to analyze modern scientific achievements in the field of anomalies of the caudal spine and syndromic diseases that are most common in medical practice, and compare them with our clinical observations. Materials and methods: A rare clinical case of caudal regression syndrome in a child was investigated. Medical history was studied by interviewing the parents, reviewing outpatient and inpatient records, and analyzing the results of clinical and laboratory tests. The primary method of examination was X-ray. For more accurate diagnosis, ultrasound, and contrast-enhanced computed tomography (with Tomohexol-350) in 3-D format were used. Our findings were compared with the results of other studies conducted over the last ten years. Results of the study and discussion: A 15-year-old girl, G., was under our observation. Her weight was 50 kg, and her height was 167 cm. A month prior to admission, she had experienced pain in the lower abdomen and lumbar spine. She became fatigued quickly, could stand and run only for short periods. The spinal axis deviated to the right in the lumbar region, with the apex of the curvature at the third lumbar vertebra, and a fixed deformity. Plain radiographs of the lumbar spine revealed multiple vertebral malformations. An ultrasound of the abdominal cavity showed a cyst on the left ovary, agenesis of the left kidney, and multiple malformations of the lumbar spine. The uterus was deformed – "bicornuate uterus". A diagnosis of caudal regression syndrome was made, and the course of the condition and treatment were described. Conclusions: A defect that develops in the early stages of embryogenesis typically leads to multiple malformations of nearby anatomical structures. This phenomenon is known as sequencing – the sequence of congenital multiple malformations, which is supported by our findings. It is clear that caudal regression syndrome may have several variants, which require further study.